Oikos: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi ISSN Online: 2549-2284 Volume 00 Nomor 0, Desember 2023 1 PENGARUH GCG DAN KINERJA KEUANGAN TERHADAP MANAJEMEN LABA YANG DIMODERASI OLEH KUALITAS AUDIT - Salwa, Farrenina; Yuli Chomsatu Samrotun; Dimas Ilham Nur Rois (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The purpose of this study was to test and analyze the influence of GCG and financial performance on earnings management as well as test and analyze the influence of GCG and financial performance on earnings management which is moderated by the audit quality variable on earnings management. This research was conducted on food and beverage subsector manufacturing companies listed on the Indonesian Stock Exchange (BEI). The sample selection method in this study used a purposive sampling method and a sample of 14 companies was obtained. The data analysis technique used in this research is multiple linear regression processed with SPSS version 21. The research results show that profitability and free cash flow have an effect on earnings management, while managerial ownership and institutional ownership have no effect on earnings management. Then, audit quality can moderate the influence of free cash flow on earnings management.